Hubungan Penerapan Model Reguler Pendidikan Kepramukaan dengan Hasil Belajar Kognitif Siswa SD: Hubungan Penerapan Model Reguler Pendidikan Kepramukaan dengan Hasil Belajar Kognitif Siswa SD - Noti Ashar; Lukman; Nani Yuliantini (Universitas Bengkulu, 2023)
This study aims to determine the relationship of applying the regular model of scouting education (x) with students' cognitive learning outcomes (y) at sd negeri 01 kota bengkulu. This type of research is quantitative research. The population of this study amounted to 41 student scout members who followed the regular model of sampling total sampling technique. Data collection techniques used questionnaires, recapitulation of weekly repeat values ​​in cognitive and documentation aspects. Research instruments were tested using validity and reliability. While prerequisite analysis test using normality test, homogeneity test, and hypothesis test. Data analysis technique is done by using